Variation of Molasses Dose in Making Solid Organic Fertilizer with Fresh Cow Dung - Karno Karno; Sunaryo Sunaryo; Frida Hendrarinata (Health Notions, 2020)
Introduction: Livestock population in Magetan, East Java Province, Indonesia is quite high, which is 58.671 animals This can be become a potency for development of organic fertilizer with fresh cow dung as the raw material. For producing biogas from cow dung, it needs to be conducted appropriate technological innovation, thus, it can be used and can reduce environmental pollution. Methods: The research’s method was eksperimental research. Purpose: Identifying the measuring the levels of: macronutrient of organic fertilizer in this research: N, P, K, and C-organic. Analyzing exact fermentation time in making organic fertilizer from variation in the comparison of molasses. Result: The organic levels of N, P, K and C showed that it qualified the standard of Regulation of the Ministry of Agriculture Number 70/ PERMENTAN / SR.140 / 102011. Based on the research result, it was obtained that the fastest of fermentation time was in variation 4 with the comparison of addition of molasses dose in 200 ml and EM4 in 50 ml. Keywords: molasses; organic fertilizer; fresh cow dung